Phytochemical and Pharmacological Evaluation of Cyperus odoratus Extract (Bangladesh Pharmaceutical Journal, 2018)
Cyperus odoratus (Family: Cyperaceae) is a 10 to 50 cm long perennial herb used as traditional medicinal plant in Bangladesh to treat various pathological conditions like piles, tumour and wound. The ethanolic extract of C. odoratus (COET) has been evaluated for different bioactivities, for example, antioxidant, analgesic, anthelmintic and cytotoxic activities. Antioxidant activity was investigated by DPPH free radical scavenging assay, analgesic activity was evaluated from ‘acetic acid induced writhing inhibition test’ in mice, anthelmintic activities was tested by ‘time of paralysis and death’ assays and cytotoxic activities was observed from the ‘brine shrimp lethality bioassay’. Total tannin and phenol contents were also measured by using Folin-Ciocalteu reagent. Phytochemical screening indicated that the presence of alkaloids, tannins, flavonoids, glycosides, proteins, gums, steroids and acidic compounds. In DPPH free radical scavenging assay the extract showed IC50 value of 8.05 μg/ml, whereas the standard ascorbic acid showed 31.40 μg/ml. The total tannin and phenolic contents were found to be 3.35 and 1.68 mg GAE/100 g of dried extract, respectively. In acetic acid induced writhing assay, the extract showed 36.23 and 61.32% writhing inhibition at doses of 250 mg/kg and 500 mg/kg body weight, respectively, whereas standard Diclofenac-Na (25 mg/kg) showed 70.03% writhing inhibition. The plant extract showed anthelmintic activity in a dose dependant manner. COET also showed LD50 against brine shrimp nauplii at 11.344 μg/mL. After observing all preliminary biological data, it has been confirmed that the plant has antioxidant, analgesic, cytotoxic and anthelmintic properties.Bangladesh Pharmaceutical Journal 21(2): 150-159, 2018